(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A cerebral aneurysm, often called a brain aneurysm, is a bulging area of a blood vessel in the brain that becomes weakened and fills with blood. This condition can exert pressure on nearby brain tissue and nerves. An aneurysm has the potential to rupture, causing blood to leak into the brain or its surrounding areas, resulting in a condition known as hemorrhage. Each aneurysm carries a risk of bursting and bleeding. When an aneurysm does rupture, it can result in severe health complications, including stroke, brain injury, coma, and even death. The study included 200 participants with an average age of 52.7 years, with a majority (60%) being female. Most aneurysms (70%) were found in the anterior part of the brain’s blood supply, while 25% were located in the posterior area, and 5% of the participants had multiple aneurysms. In more than half of the cases (58%), the first sign was bleeding in the region surrounding the brain. Surgical clipping of the aneurysm resulted in complete closure in 95% of cases, with a 4% chance of recurrence within five years. A less invasive procedure known as coiling initially obstructed the aneurysm in 90% of instances, but had a higher recurrence rate of 12%. The overall death rate among the patients was 7%, which was notably higher for those whose aneurysms had ruptured.